Interstitial cystitis – a diagnostic dilemma: A case report (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Interstitial cystitis is a debilitating condition with a rising prevalence due to increasedresearch and diagnostic criteria. Interstitial cystitis falls under the category of urologic chronic pelvic painsyndrome and is a diagnosis of exclusion. Interstitial cystitis or bladder pain syndrome (BPS) ischaracterized by chronic inflammation. Common symptoms include chronic pelvic pain, pressure, ordiscomfort perceived to be related to the urinary bladder accompanied by other urinary symptoms, suchas persistent urge to void or urinary frequency in the absence of confusable diseases (hypersensitivebladder symptoms). The true burden of interstitial cystitis is underestimated, and the economic burden ofthe disease is due to multiple office visits and an increase in direct medical costs.Case presentation: A 59-year-old para 2+0 (2 previous scars) postmenopausal with a 1-year history offrequency (up to eight episodes) nocturia with low abdominal pain. Her urinalysis profile, urea,electrolytes and creatinine, and ultrasound and computed tomography of the kidneys, ureters andbladder, pap smear, and random blood sugar tests were unremarkable. Cystoscopy was hemorrhagicwith biopsy histology showing ulcerated bladder mucosa with numerous plasma cells, eosinophils, andneutrophils in the lamina propria no atypia, with fibrosis and dilated capillaries in the lamina propria. Onfollow-up she had a recurrence of pain symptoms with a cystoscopy biopsy, seven months later showingplasma cell infiltrate with ulceration of the overlying urothelium, and congestion of the blood vessels. Shewas not neoplastic and was put on antihistamine, nonsteroidal antiinflammatory drugs, and solifen.Conclusion: Prompt diagnosis and treatment of interstitial cystitis will reduce the burden of diseaseassociated with multiple outpatient visits and unnecessary use of antibiotics. The mainstay ofmanagement is oral and intravesical treatment with surgery in refractory cases.